TAKTIK PEMBELAJARAN SENI MUSIK UNTUK KELAS 9 - Martiati, Lucy; Tama Nyguel, Steven; Ikasari Ichwan, Clemy (Program Studi Pendidikan Musik, 2023)
The purpose of this study was to find out the learning process of musical arts used in teaching 9th grader students at Candle Tree Junior High School for the 2022/2023 academic year. Time and place of research starting from November 2022 to January 2023 at Candle Tree Junior High School. The research method used is a qualitative research method. Data collection uses observation, interview, documentation, and triangulation techniques. Data analysis was conducted by making field notes, making interview transcripts, compiling and searching for data from pre-recorded interviews, then transcribing interview transcripts in table form, making field notes and searching for data, as well as documenting. The results of the research showed that the learning process of musical art used in teaching 9th graders uses the discussion learning method, the demonstration method, and the drill method. The advantage of using this method is that students are activated through discussion, students pay attention to teacher demonstrations, then immediately try to practice. Giving motivation is also conducted, and educators listen to students' input in determining song material.